Implementasi Aplikasi Simpeldesa Sebagai Sarana Publikasi di Desa Tambak Kalisogo - Rizky Sinta Nuriyah; Lailul Mursyidah (LPPM Universitas Abdurrab, 2026)
This study analyzes the implementation of the Simpeldesa application as a digital publication platform in Tambak Kalisogo Village, Jabon District, Sidoarjo Regency. The main challenges include limited digital literacy among village officials and residents, a lack of active village journalists, low community participation in accessing official village platforms, and limited managerial capacity in application management. This study aims to assess the effectiveness of Simpeldesa implementation using the policy implementation theory proposed by George C. Edwards III, which emphasizes four key factors: communication, resources, implementers’ disposition, and bureaucratic structure. A qualitative research approach was employed, with data collected through interviews, observation, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that Simpeldesa has contributed positively to enhancing transparency and the dissemination of village information. Communication and coordination among implementers were relatively effective and supported by a responsive attitude from village officials. However, limitations in human resource capacity and the absence of formal regulations remain significant constraints. Therefore, strengthening digital literacy, enhancing the capacity of village officials, and establishing formal regulatory frameworks are essential to support sustainable village e-government implementation.